Emotion episodes during psychotherapy sessions among women newly diagnosed with gynecological cancers. Issue 9 (17th December 2014) - Myers Virtue, Shannon; Manne, Sharon L.; Darabos, Kathleen; Heckman, Carolyn J.; Ozga, Melissa; Kissane, David; Rubin, Stephen; Rosenblum, Norman
Abstract Objective The aim of this study was to describe emotion episodes during early and late psychotherapy sessions among women newly diagnosed with gynecological cancer and to examine whether the total number of emotion episodes during early and later sessions was associated with baseline psychological distress, dispositional emotion expressivity, and patient‐rated therapeutic progress. Methods The study utilized data from an ongoing study examining the efficacy of two psychotherapy interventions, a coping and communication intervention and a supportive counseling intervention, for women diagnosed with gynecological cancer. Emotion episode coding was completed for the first and sixth psychotherapy sessions for each patient randomized to receive psychotherapy (N = 173). Patients completed baseline survey measures of psychological distress and dispositional emotional expressivity and post‐session ratings of therapeutic progress. Results The average number of emotion episodes was 7.4 in the first session and 5.2 episodes in the sixth session. In both sessions, the majority of emotion episodes contained only negative emotions and focused on a cancer‐related topic. A higher number of emotion episodes in the first session was associated with higher psychological distress reported in the baseline survey (p = 0.02). A higher number of emotion episodes in the sixth session was associated with a higher number of emotion episodes in the first session (p < 0.001) and higher patient‐rated progress as rated in the sixth session (p = 0.016). Conclusion The findings highlight the importance of expressed emotions, particularly negative emotions about cancer‐related topics, in therapeutic progress during psychotherapy among women diagnosed with gynecological cancer. Copyright © 2014 John Wiley & Sons, Ltd.